Identity politics in the Middle East liberal thought and Islamic challenge in Egypt - Hatina, Meir (Library of modern Middle East studies, 2007)
Here Meir Hatina sheds light on the issue of Islam in the state through the prism of Egypt during the twentieth century. He traces the continuity of Egyptian liberalism, from its emergence during the first half of the century through its repression following the July 1952 revolution, to the rise of secular liberalists such as Faraj Fuda in post-revolutionary Egypt. 'Identity Politics' reveals the assertive nature of the Islamic struggle, the desire to remake the state by fostering a close affinity between faith and power, worship and politics, which holds contemporary resonance for all Middle Eastern states.